People watching social, perceptual, and neurophysiological studies of body perception - Johnson, Kerri L.; Shiffrar, Margaret (New York : Oxford University Press, 2013)
The human body has long been a rich source of inspiration for the arts, and artists have long recognized the body's special status. While the scientific study of body perception also has an important history, recent technological advances have triggered an explosion of research on the visual perception of the human body in motion, or as it is traditionally called, biological motion perception. This book provides an integration of theory and findings that clarify how the human body is perceived by observers.
Description based on online resource; title from home page (viewed on Dec. 14, 2012).
Includes bibliographical references and index.
Keywords: Perception; Body image; Neurophysiology